EFFECTIVENESS OF USING DIGITAL MEDIA IN LEARNING INDONESIAN LANGUAGE IN SECONDARY SCHOOLS - -M. Iqbal Tawakkal, Djoko Apriyono (STAI Syaichona Moh. Cholil Bangkalan, 2025)
The integration of digital media in education has transformed the way students engage with learning materials, particularly in language instruction. This study aims to analyze the effectiveness of using digital media in the teaching of Indonesian language at the secondary school level. Employing a quantitative descriptive approach, data were collected through surveys and observations in several junior and senior high schools. The results indicate that the use of digital media, such as interactive applications, online learning platforms, and multimedia resources, significantly enhances student motivation, participation, and comprehension. Moreover, digital media supports differentiated instruction, allowing teachers to accommodate various learning styles. However, challenges such as limited access to technology and lack of digital literacy among teachers still hinder optimal implementation. This study concludes that digital media is an effective tool in Indonesian language learning at secondary schools when supported by adequate infrastructure and teacher readiness.